OPTIMIZATION OF THE PRINCIPAL'S ROLE AS A SUPERVISOR TO IMPROVE THE PERFORMANCE OF TEACHERS IN SURAKARTA - Meti Fatimah; Mustofa Mustofa; Rizkiy Pratama Putra; Mansur Muhammad Abu Zinah; Mowafg Masuwd (Profetika: Jurnal Studi Islam, 2023)
One way to develop the ability of teacher resources is through supervision. Supervision is an effort to provide services to teachers in elementary to high schools both individually and in groups. This study aims to determine the extent to which school principals as supervisors improve teacher performance. This research is descriptive qualitative research. Descriptive qualitative research is analyzing and presenting facts systematically so that they are easier to understand and conclude. The subjects of this study were teachers at the Surakarta Islamic Center Jajar Educational Institution. The Jajar Islamic Center Educational Institution is an institution that is oriented towards Da'wah, educational and social activities based on the Al Quran and As-Sunnah according to the understanding of salafush saleh. Data was obtained through observation, interviews and documentation as well as the results of relevant literature. This analysis is divided into several stages data collection, data reduction, data presentation, and conclusion. The results of this study show 1). At the Jajar Islamic Center, the principal as a supervisor conducts training for teachers using teaching demonstrations, workshops, training, observation, individual and group conferences, as well as supervision visits. In addition, supervision is also implemented at the Jaguar Islamic Center with an Islamic Da'wah perspective based on the Al-Qur'an letter A-Nahl verse 125. 2). The principal as a supervisor in improving teacher performance with authority in academic supervision which is the responsibility of the supervisor and is carried out with a clear schedule, both in terms of period and time. In addition, supervisors conduct research, assessment, improvement and development related to the learning process to develop teacher professionalism and provide motivation for teachers to make performance improvements.